Should We Move Up the Clock on Preventive Intervention in Marfan's Disease? - Robicsek, Francis (The Thoracic and Cardiovascular Surgeon, 2020)
Gradual dilatation of the ascending aorta is a common phenomenon in patients with Marfan's disease, which often leads to dissection and rupture. It is estimated that around two-thirds of the patients either die or require major surgery before the age of 42 years. In the mirror of the experience of 40 years with aortic wall reinforcement, the author forward the postulate that whenever the ascending aorta of an individual with proven Marfan's disease reaches adult size, that is, approximately 3.5 cm in diameter, the wall of his/her ascending aorta should be reinforced to prevent further expansion.
Keywords: Marfan’s disease; ascending aorta